2018
DOI: 10.5604/01.3001.0011.6146
|View full text |Cite
|
Sign up to set email alerts
|

The Very Low Frequency of Epstein-Barr JC and BK Viruses DNA in Colorectal Cancer Tissues in Shiraz, Southwest Iran

Abstract: Viruses including Epstein-Barr virus (EBV), JCV and BKV have been reported to be associated with some cancers. The association of these viruses with colorectal cancers remains controversial. Our objective was to investigate their infections association with adenocarcinoma and adenomatous polyps of the colon. Totally, 210 paraffin-embedded tissue specimens encompassing 70 colorectal adenocarcinoma, 70 colorectal adenomatous and 70 colorectal normal tissues were included. The total DNA was extracted, then qualif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 37 publications
4
37
2
Order By: Relevance
“…In the present study 10% of CRC of patients were positive for JCV DNA and was in agreement with results reported by Mou et al, (2012) in China. Sarvari et al, (2018) have reported low prevalence of 1.42% JCV DNA in patients with CRC, in Shiraz city, Iran, which was lower than our finding. In the present study the rate of JCV DNA was among the male (7.5%) and female (2.5%) patients (p=0.29%).…”
Section: Discussioncontrasting
confidence: 96%
“…In the present study 10% of CRC of patients were positive for JCV DNA and was in agreement with results reported by Mou et al, (2012) in China. Sarvari et al, (2018) have reported low prevalence of 1.42% JCV DNA in patients with CRC, in Shiraz city, Iran, which was lower than our finding. In the present study the rate of JCV DNA was among the male (7.5%) and female (2.5%) patients (p=0.29%).…”
Section: Discussioncontrasting
confidence: 96%
“…A Chinese study of 137 samples described a rate of infection in CRC of 40.9% [13]. But in contrast, a large American study failed to prove JCV infections in 233 patient samples [29] and a study from Iran described a positive detection rate of only 1.46% (2 of 70 patients) [30]. Our own results are pretty much in line with the latter ndings and also indicate that JCV is unlikely involved in CRC development.…”
Section: Discussionsupporting
confidence: 82%
“…The authors used PCR to examine 35 colon samples (Fifteen CRCs and twenty adenomas) and failed to detect any positive cases. Similar results were obtained in a study by Sarvari et al 19 ( Table 1).…”
Section: Status Of Ebv In Colorectal Cancersupporting
confidence: 92%
“…Therefore, we believe that studies exploring EBV presence and role in colorectal adenoma-carcinoma sequence are largely missing and may significantly contribute to a better knowledge on the role of EBV in colorectal carcinogenesis. A recent study of Sarvari et al 19 revealed very low EBV positivity in invasive colorectal carcinomas (1.4%) while all corresponding colorectal adenomas (n = 70) as well as adjacent normal colonic mucosa (n = 70) were negative for EBV. Similarly, Mehrabani-Khasraghi et al 21 reported no EBV expression in any carcinomas or adenomas they investigated.…”
Section: Discussionmentioning
confidence: 93%